(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Eremetova K. Keywords: names of natural phenomena, etymology, semantic evolution, synonymy. The article is devoted to the study of etymological and semantic peculiarities of the words denoting the natural phenomenon ‘hurricane’ and other similar natural phenomena. The number of these words has been growing for centuries: some words have become obsolete; other words have acquired new meanings. Thus, the semantic evolution is a perpetual process.